1998
DOI: 10.1212/wnl.51.4.1110
|View full text |Cite
|
Sign up to set email alerts
|

The spectrum of antecedent infections in Guillain-Barré syndrome

Abstract: Recent infections with C. jejuni, cytomegalovirus, Epstein-Barr virus, and M. pneumoniae are specifically related to GBS. The variety of infections may contribute to the clinical and immunologic heterogeneity of GBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
591
14
19

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 759 publications
(647 citation statements)
references
References 15 publications
23
591
14
19
Order By: Relevance
“…In our study, ages were uniformly distributed within an age range of 2-12 years which is not in accordance with studies by Rees et al, Italian Guillain-Barré Syndrome Study Group and Van Koningsveld et al where the incidence of GBS was found to increase with the age 2,6,7 . In studies by Jacobs et al and Farhoudi et al, the percentage of patients with preceding illness was 70% in comparison to 39% in our study 5,8 . In the study by Farhoudi et al, quadriparesis was seen in 91% and paraparesis in 07% whereas in our study 67% had quadriparesis and 33% had paraparesis 5 .…”
Section: Studies By Rees Et Al Yuan Et Al and Rocha Et Alcontrasting
confidence: 72%
“…In our study, ages were uniformly distributed within an age range of 2-12 years which is not in accordance with studies by Rees et al, Italian Guillain-Barré Syndrome Study Group and Van Koningsveld et al where the incidence of GBS was found to increase with the age 2,6,7 . In studies by Jacobs et al and Farhoudi et al, the percentage of patients with preceding illness was 70% in comparison to 39% in our study 5,8 . In the study by Farhoudi et al, quadriparesis was seen in 91% and paraparesis in 07% whereas in our study 67% had quadriparesis and 33% had paraparesis 5 .…”
Section: Studies By Rees Et Al Yuan Et Al and Rocha Et Alcontrasting
confidence: 72%
“…The disease diversity is associated with the variety in preceding infections. Campylobacter jejuni is the predominant infection triggering GBS worldwide,14 and is associated with severe acute motor axonal neuropathy (AMAN)‐type of GBS with a poor clinical outcome 15. Cytomegalovirus in contrast can cause severe senso‐motoric disorders and a GBS subtype described as acute inflammatory demyelinating polyneuropathy (AIDP) 16.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our results are not in accordance with those published by Jacobs, van Doorn, Groeneveld, Tio‐Gillen, & van der Meche (1997), Jacobs et al. (1998). They reported that anti‐GM2 IgM antibodies were found more often in patients with GBS with CMV infection (22%) than in patients without the infection.…”
Section: Discussionmentioning
confidence: 99%